Pengaruh Faktor Keperilakuan Organisasi Terhadap Kegunaan Sistem Akuntansi Keuangan Daerah (Studi Kasus Pada Kantor Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Sikka) - Aloysius Theofilus Indrianto Max Pare; Maria Nona Dince; Emilianus Eo Kutu Goo (Jurnal Riset Akuntansi, 2023)
This research aims to test and analyze the effect of training, explaining the objectives and support of superiors on the usefulness of regional financial accounting systems. This type of research is quantitative research. The population in this study were civil servants at the Sikka Regency BPKAD office, with a sampling technique using saturated samples so that the number of samples in this study was 51 people. The data used in the research are primary data and secondary data using data collection methods, namely questionnaires. Data management in this research is multiple linear regression analysis using the SPSS software program. The results of this study indicate that training (X1), clarity of objectives (X2) and support from superiors (X3) partially influence the regional financial accounting system (Y) and also training (X1), clarity of objectives (X2) and support from superiors (X3 ) have a simultaneous effect on the regional financial accounting system (Y)